Registration verification using image of an object / Sabariah Rawi - Rawi, Sabariah (Faculty of Computer and Mathematical Sciences, 2007)
The globalization era today contributes to the development of online communications. There are a lot of registration processes that can be done via online. There is a problem that usually occurs when the online method is implemented. There is a situation where the system is spammed by the automated system. As the result, the administration that is responsible to the process will face a problem with the form that is not completed by the human, but completed by the automated system. Therefore, the researcher was called to develop a document verification module that using image of an object. This prototype of document verification called Document Verification Using Image of an object was developed to help the administrator of the online form to prevent their system from being spammed. In this prototype, the user who want to submit the registration form have to prove that he or she is human, not automated system. He or she has to choose a word in a list which matches with the image of an object that shown in a box at the button of the registration form. If he or she chooses the right word, the form will be processed, but if the test is unsuccessful, he or she has to try it again. So that, the administrator just need to process the forms there are successfully submitted into the database. In order to acquire the feedback from the user, an interview has been done among the respondents who have tested the prototype. From the findings, majority of the respondents agree that it is easy and fun to use the module. It can be conclude that majority of them are accept the verification using image of an object as a verification method.